ANALISIS KOMPETENSI GURU DALAM PEMBELAJARAN PROBLEM BASED LEARNING IPAS DI SEKOLAH DASAR - Insiano, Dewi Angraini (Universitas Tanjungpura, 2025)
This research was motivated by observations of primary school learning that has not been optimal in implementing a student-centered approach and utilizing innovative media. The main objective of this research is to conduct an in-depth analysis of the competence of a fourth grade teacher at SD Negeri 2 Momunu in implementing the Problem Based Learning (PBL) model in Natural and Social Sciences (IPAS). This research uses a descriptive qualitative approach. Data were collected through three main techniques: in-depth interviews with teachers, participatory observations in the classroom, and analysis of documents related to learning planning and implementation. The results of the study indicate that teachers have systematically implemented all five phases of PBL. These phases include: (1) providing students with a clear orientation regarding the problem to be solved, (2) organizing students into effective learning groups, (3) providing guidance and support during the inquiry process, both individually and in groups, (4) facilitating students in developing and presenting their work, and (5) guiding students in analyzing and evaluating the process and results of problem solving. The findings from the three data sources show that teachers have good competence in planning, implementing, and evaluating PBL learning. Teachers are able to create a learning environment that encourages students to be actively involved in problem solving, collaboration, and the development of critical thinking skills. Nevertheless, this study also identifies several areas that can still be improved, such as the varied use of learning media and increased student involvement in the reflection process. This study contributes to the understanding of PBL implementation at the elementary school level and can be a reference for the development of teacher professionalism.